PENGARUH REPUTASI MANAJEMEN PUNCAK DAN DEWAN KOMISARIS TERHADAP PENILAIAN INVESTOR PADA PERUSAHAAN YANG MELAKUKAN IPO - Sumiyana, Rias Aini (UI Scholars Hub, 2008)
This research empirically examines the influence of reputation of top management and board ofcommissioner (BOC) on firm value. Top management has a primary role as a strategic decision maker in a firm. Its actions and characteristics specifically influence the organization ’s outcomes. The main duty of BOC is to ensure that managerial decisions are consistent with shareholders goals. One indicator of top management and BOC ’s competency and skill is reputation. The purpose of the study is to investigate the influence of reputation of top management and BOC on firm value at the Initial Public Offering (IPO). Its effect is through a largely symbolic role to enhance organizational legitimacy and it provides a signal to potential investors about the firm s prospect. The samples include 59 firms undertaking IPO in the Jakarta Stock Exchange (JSX) during 1999-2006. This study employs three characteristics of reputation: education background, previous experiences and corporate board experiences. This study finds that education background has a positive association with investor valuation. Previous experiences and corporate board experiences do not have significant association with investor valuation.